Between Cyborg and Larva: A Vicious Circle That Human Beings Experience in the Post-humanist Era - Chukurov, Andrey (Slavica, 2018)
The article reveals the reasons for and specific features of the transition to the posthumanistera. The author of the study reviews the criticism of classical humanism and analyzesthe relationship between the concepts of "trans-humanism" and "post-humanism." In asituation in which a permanent identity is impossible and people move to a “current” “unstable”identity, the Imaginary becomes the main guideline for the self-identification process.Human beings are unable to cope with the challenges of our time and are aware of their owninferiority. That is why they are trying to improve themselves through the available bodymodifications. However, this process gives them a new panic attack over the potential lossof control over the body. Analyzing these processes, the author turns to the most controversialand specific phenomenon of popular culture – "body horror". This genre reveals the deeplayers of consciousness, fears and insecurity of human beings in the post-humanist era.